Evaluation on the Effectiveness of Safe Work Practices (SWP) Via Observation and HIRARC Analysis at Assembly Process Area in Manufacturing Industry - MOHD AMRI BIN LAJIS, MUHAMMAD QARNI BIN MOHD AMRI; ALIFF HISYAM BIN A RAZAK; MOHD AZWADI BIN MOHAMAD KHAIR (Progress in Engineering Application and Technology, 2023)
A manufacturer was a manufacture of finished goods from raw materials used a variety of tools, equipment, and processes and then sells those goods to consumers. The manufacturing sector had grown and increased, and the potential dangers to human physical and health, property, and the environmental posed by its operations and production activities had created increased awareness and brought safety issues among industry, government, and the public. AAC (Autoclaved Aerated Concrete) manufacturing for Assembly department area was selected for this studied to evaluate the effectiveness of safe work practices associated with the daily process of activities. The objectives of this studied were to identify worker’s behavior and work practice at assembly-process area before implement Safe Working Procedure (SWP), to propose few procedures of Safe Working Procedure (SWP) based on identified worker’s behavior and common work practice at assembly-process area and to evaluate the worker’s behavior and work practice after implementation of Safe Working Procedure (SWP) assembly-process area. For this studied, hazard identification of potential hazards had been identified. The risk valued was a metric used in risk assessment that assigns a specific valued to the importance of each identified hazard. The studied reveals that the assembly process was exposed to some hazards during the process of assembling. This includes physical hazards, ergonomic hazards and health hazards. Finally, SWP methods have been conducted such as safety briefing, training and counselling session to evaluate the SWP effectiveness at assembly department area.